2015
DOI: 10.1002/lno.10199
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transport and reactivity within a sandy seepage face in a mesotidal lagoon (Ria Formosa, Southwestern Iberia)

Abstract: Sandy sediments are now recognized as sites of high carbon turnover enhanced by porewater flow. However, it is unclear how coupling between porewater advection and benthic metabolism might permit O2‐saturated areas and suboxic environments to coexist in close proximity. Field sampling campaigns, flow‐through reactor (FTR) experiments and diagenetic modeling were used to study benthic O2 dynamics in surface sediments of a permeable intertidal seepage face (Ria Formosa; Southwestern Iberia). Field results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 50 publications
7
33
0
Order By: Relevance
“…However, Beck et al (2017) indeed found 60 -100% oxygen saturation in pore water from the top 5 cm of the ridge (corresponding to In-2 of our study) in May 2014. It should be noted that another study on a mesotidal beach at the Portugese Atlantic coast, reported high oxygen levels (>50%) even in the lowest exfiltration zone, which they attributed to an interplay of strong tidal oscillations, rapid advection, and low organic matter supply (Ibanhez and Rocha, 2016). In our study, we did observe some patches with relatively elevated oxygen values in the ridge-runnel area (light blue spots in Figure 4), but they always remained well below 50%.…”
Section: Biogeochemical Patternssupporting
confidence: 58%
“…However, Beck et al (2017) indeed found 60 -100% oxygen saturation in pore water from the top 5 cm of the ridge (corresponding to In-2 of our study) in May 2014. It should be noted that another study on a mesotidal beach at the Portugese Atlantic coast, reported high oxygen levels (>50%) even in the lowest exfiltration zone, which they attributed to an interplay of strong tidal oscillations, rapid advection, and low organic matter supply (Ibanhez and Rocha, 2016). In our study, we did observe some patches with relatively elevated oxygen values in the ridge-runnel area (light blue spots in Figure 4), but they always remained well below 50%.…”
Section: Biogeochemical Patternssupporting
confidence: 58%
“…At station A, the lower salinity values in NO 3 − was the predominant form of porewater DIN throughout the studied period (Figure 5), as expected given the near-saturation of oxygen inside the beach (see Supplementary Figure 3; Ibánhez and Rocha, 2016). Significant reductions in oxygen levels during active seepage are only found in association with particulate organic matter (POM) enrichments near the sediment surface (Ibánhez and Rocha, 2016). NO 3 − distribution within the seepage face follows two different patterns during the year: from December 2009 to July 2010, NO 3 − porewater concentrations were lower than 15 µM and generally peaked close to the sediment surface.…”
Section: Porewater Solute Distribution At the Seepage Facesupporting
confidence: 75%
“…The exception occurred in January, where the lowest salinities within the beach are found at the shallower screened depths at station B (Figure 5.5). At station A, the lower salinity values in NO 3 − was the predominant form of porewater DIN throughout the studied period (Figure 5), as expected given the near-saturation of oxygen inside the beach (see Supplementary Figure 3; Ibánhez and Rocha, 2016). Significant reductions in oxygen levels during active seepage are only found in association with particulate organic matter (POM) enrichments near the sediment surface (Ibánhez and Rocha, 2016).…”
Section: Porewater Solute Distribution At the Seepage Facesupporting
confidence: 61%
See 1 more Smart Citation
“…The question is then, whether too high disturbance amplitudes or frequencies, for example by storm events or high-energy waves, have a negative influence on the adaptation capacities of the microbial community. So far, a comparison of research literature from different types of environments indicates that frequent disturbances of flow paths and sediment structures enhance, rather than restrict, microbial remineralization processes in high-energy STEs (McLachlan, 1982;Charbonnier et al, 2013;Reckhardt et al, 2015;Ibánhez and Rocha, 2016;Waska et al, 2019b). If there is no upper limit to microbial resilience against physical disturbances (Novitsky and MacSween, 1989;Degenhardt et al, 2020), then meso-to macrotidal STEs with strong wave action should be particularly active sites of organic matter turnover along the world's coastlines.…”
Section: Introductionmentioning
confidence: 99%